PROSPECTING THE ISLAMIC GENERATIONS THROUGH BEDIUZZAMAN SAID NURSI’S VISION - Said, Mohamed Mohamed Tolba; Umachandran, Krishnan (International Journal of Economics, Business, and Entrepreneurship, 2018)
The Islamic business owners and intellects wished Islam to play a superior part in the description for shared virtuousness in the economic processes. A cross-influence established with Muslim cultural values created a liberal and market oriented Western pattern of development facilitating the Islamic entrepreneurs and intellectuals to pursue contentment not only in the afterlife but also in earthly living. Bediuzzaman Said Nursi was a missionary who educated that Muslims must not discard modernity nonetheless discover newer stimulus in the blessed manuscripts to involve through it. Anticipating the development of political Islam required moderate and pro-Western Islam with sufficient materialistic liberalism to support economic development, thus necessitating the compatibility of Islamic ideas and practices with the market economy and complex web of businesses lead to an operative and post-developmental policy that requires self-governing, clear and responsible in interface with culture and economy. It should control unrestricted market which is constructive, untarnished, inspiringly causative to economic growth, socially protective and impartial to the enterprise and people Bediuzzaman Said Nursi was instrumental in the development thrust areas where the silent Muslim majority also required financial support for Islamic-oriented newspapers, television, and radio stations which were felt as a parallel modernity to the distinct world views and their life-styles by the way of clothing, taste, music, food, residential areas, vacation hotels, and the like. This paper analysis the Islamic thinking and its orientation for such development envisioned by Bediuzzaman Said Nursi in current commercial standings to achieve a very competitive edge with the western world.